The Use of a Replicating Virus Vector For in Planta Generation of Tobacco Mosaic Virus Nanorods Suitable For Metallization - Saunders, Keith; Thuenemann, Eva C.; Shah, Sachin N.; Peyret, Hadrien; Kristianingsih, Ruth; Lopez, Sergio G.; Richardson, Jake; Lomonossoff, George P. (Frontiers in Bioengineering and Biotechnology, 2022)
The production of designer-length tobacco mosaic virus (TMV) nanorods in plants has been problematic in terms of yields, particularly when modified coat protein subunits are incorporated. To address this, we have investigated the use of a replicating potato virus X-based vector (pEff) to express defined length nanorods containing either wild-type or modified versions of the TMV coat protein. This system has previously been shown to be an efficient method for producing virus-like particles of filamentous plant viruses. The length of the resulting TMV nanorods can be controlled by varying the length of the encapsidated RNA. Nanorod lengths were analyzed with a custom-written Python computer script coupled with the Nanorod UI user interface script, thereby generating histograms of particle length. In addition, nanorod variants were produced by incorporating coat protein subunits presenting metal-binding peptides at their C-termini. We demonstrate the utility of this approach by generating nanorods that bind colloidal gold nanoparticles.